Design in Gunther Kress’s social semiotics (London Review of Education, 2022)
Gunther Kress’s multimodal and social semiotic theory of communication has moved beyond the realm of linguistics, which originally framed his work, and has reached out to inform other fields, such as those of education, museum studies, as well as the humanities and social sciences more broadly. This article brings together our insights in relation to a concept from Gunther Kress’s theory, that of design. Drawing from our research, we reflect on Kress’s conceptualisation of design in social semiotics and discuss how this idea has inspired us to advance research across the domains of formal learning in schools, informal learning and communication in museums, and in everyday communication and social interaction. We consider that the contribution of design is to challenge the boundaries of concepts such as ‘competence’, ‘interpretation’ and ‘critique’, associated respectively with the dominant discourses and practices in the worlds of education, museums and everyday communication and research practice. We look at design as: (1) learning; (2) transformation of resources; and (3) an engaged and engaging social semiotic research, and argue that as an interpretative resource it enables us to move beyond the limitations posed by institutions such as schools, museums and academia.